Analogue model of gravity driven deformation in the salt tectonics zone of northeastern Mexico - Diego Gracia-Marroquín; Mariano Cerca; Dora Carreón-Freyre; Bernardino Barrientos-García (Revista Mexicana de Ciencias Geológicas)
In the deep seated gravity-driven deformation systems of the Gulf of Mexico contemporaneous extension and contraction of the overburden is favored by mechanical decoupling from the basement along thick salt sequences (up to 4 km). The updip extension is located inland, on the continental shelf of northeast Mexico, and is characterized by extensional listric faults and roll-overs; the downdip shortening zone is located at the deep waters and is characterized by a fold and thrust belt detached above the salt layer. Two physical experiments are used to discuss some aspects of these gravity-driven systems. The experimental setup includes a motor-driven experimental table, an inclined brittle basement (1°), a silicone layer simulating the salt sequences, and sand layers simulating the pre-kinematic Jurassic-Cretaceous strata before Laramide shortening. Deformation resulted in further tilting of the basement (3° to 4°). After the onset of deformation, thin sand layers were added at regular time intervals simulating the syntectonic sedimentation. The experiments reproduced the geometry of the deformation at the frontal ramp characterized by a seaward vergent thrust and its associated deformed region (the Perdido fold belt). The fold and thrust belt localization was favored by the change in basement inclination (a built-in slope change). Key elements interpreted in one available section of the area were reproduced in the model: a) the presence of an antithethic roll-over in the extensional zone and, b) the basinward vergence of folds and thrusts observed in the downdip shortening zone in the mexican Perdido fold belt.